Physical activity pattern and its influencing factors among patients with inflammatory bowel disease in East China - Ying Zhou; Feng Xu; Liyan Xu; Huiwei Liu; Xie Zhang (BMJ Open)
Objective To investigate the current level of physical activity (PA) and its influencing factors among patients with inflammatory bowel disease (IBD) in East China.Design Cross-sectional study.Setting Questionnaire survey recruiting from six tertiary referral hospitals in East China between October and December 2023.Participants Patients with Crohn’s disease (CD) or ulcerative colitis (UC) aged 18–65 years without conditions limiting PA engagement.Primary and secondary outcome measures Primary outcomes comprised total PA, PA levels and sedentary time over 1 week. Demographic and clinical characteristics, disease-related and non-disease-related barriers to PA, and PA outcome expectation score were also assessed.Results Of 391 eligible respondents, including 271 CD (69.3%) and 237 males (60.6%), the median total PA in IBD patients was 594 (0–1695) metabolic equivalent of task (MET)-min/week, with 53 patients (13.6%) of high, 140 (35.8%) of moderate and 198 (50.6%) of low level. The median sedentary time was 2325 (1500~3120) min/week in IBD patients, with CD significantly more than UC (p<0.01). A total of 180 IBD patients (46.0%) had reduced total PA after diagnosis, 134 (49.4%) in CD and 46 (38.3%) in UC (CD vs UC, p<0.05). Multifactorial logistic regression analysis showed that gender (OR=1.704, 95% CI 1.132 to 2.565, p=0.011) and PA outcome expectation score (OR=1.176, 95% CI 1.090 to 1.270, p<0.01) were independent influencing factors of PA levels in patients with IBD.Conclusion In East China, total PA and proportion of moderate- to high-level PA in IBD patients was considerably low. Compared with UC, CD patients had longer sedentary time and more postdiagnostic PA reduction. Gender and PA outcome expectation scores were independent influencing factors on PA levels in IBD patients. These results pointed to potential patient populations for future-focused interventions.